2018
DOI: 10.1002/jmri.26221
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion diffusion‐weighted MRI of invasive breast cancer: Correlation with prognostic factors and kinetic features acquired with computer‐aided diagnosis

Abstract: Background As both intravoxel incoherent motion (IVIM) modeling and dynamic contrast‐enhanced magnetic resonance imaging (DCE‐MRI) provide perfusion parameters, IVIM‐derived perfusion parameters might be expected to correlate with the kinetic features from DCE‐MRI. Purpose To investigate the association between IVIM parameters and prognostic factors and to evaluate the correlation between IVIM parameters and kinetic features in invasive breast cancer patients using computer‐aided diagnosis (CAD). Study Type Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
4
13
1
Order By: Relevance
“…Tumor diameter and lymph node metastasis can also affect the treatment and prognosis of breast cancer. However, both in this study and previous reports 35–37 none of the aforementioned factors showed a significant correlation with derivative parameters of IVIM and APTWI, indicating that IVIM and APTWI do not have the capability to comprehensively evaluate the prognostic factors of breast cancer.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Tumor diameter and lymph node metastasis can also affect the treatment and prognosis of breast cancer. However, both in this study and previous reports 35–37 none of the aforementioned factors showed a significant correlation with derivative parameters of IVIM and APTWI, indicating that IVIM and APTWI do not have the capability to comprehensively evaluate the prognostic factors of breast cancer.…”
Section: Discussioncontrasting
confidence: 95%
“…As a result, the D value was lower than that in the group with low Ki‐67 expression. However, in other studies 27,36 no significant correlation between the D value and the expression of Ki‐67 was observed. We speculated that this discrepancy might be related to the inclusion of lesions, the selection of the b‐values for IVIM, and the delineation of the ROI.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…proved ADC to be a valuable noninvasive quantitative biomarker for assessing BC invasiveness ( 25 ). Agreeing with previous studies ( 26 – 29 ), our results showed that a lower ADC was associated with higher tumor malignancy, especially in TNBC patients. This phenomenon may be attributed to the high cellular density and the restriction of water molecules in malignant tumors ( 30 ).…”
Section: Discussionsupporting
confidence: 90%
“…In the diffusional kurtosis imaging (DKI) model first proposed by Jensen et al (17), when the bvalue is high (>1000 s/mm 2 ) the diffusion of water molecules follows a non-Gaussian distribution, the DKI model is more accurate at assessing the diffusion of water molecules in a lesion (17)(18)(19). In recent years, extended DWI models based on different b-values, including IVIM and DKI, have been used for the identification of tumors in liver (20), prostate (21,22), thyroid (23) and brain (24). However, there have been few studies combining ADC, IVIM, and DKI values for use in the differentiation of benign and malignant breast lesions.…”
Section: Introductionmentioning
confidence: 99%